How to Minimize Ischemic Complication Related to Swollen Temporalis Muscle Following Indirect Revascularization Surgery in Moyamoya Disease: A Technical Report - Joo, Sung Pil; Kim, Tae Sun; Moon, Hyung Sik (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background There are several reports in the literature of postoperative ischemic events due to swelling of the temporalis muscle after indirect revascularization surgery. Here, we report our surgical technique for preventing ischemic events during the acute postoperative recovery period in moyamoya patients.Material and Methods We used various types of titanium mesh to cover the bony defect area in 8 patients (10 operations) with moyamoya disease. The mesh was cut and manipulated according to the shape of the bony defect.Results Surgical results were favorable, with no newly developed ischemic event or infarction in the acute recovery period. The mesh formed an outer table of skull, so there was no compressive effect on the temporalis muscle and no cosmetic defects.Conclusions The titanium mesh appears to be effective and useful for prevention of ischemic insult in the treatment of moyamoya disease. The choice of this procedure depends on both the operative findings of temporalis muscle thickness and the status of ischemic vulnerability of moyamoya brain.
Keywords: moyamoya disease; temporalis muscle; indirect revascularization; swelling